“Missionary for Culture”: Walter Abell, Maritime Art and Cultural Democracy, 1928-1944 - Niergarth, Kirk (Acadiensis, 2006)
During his years in Nova Scotia, Walter Abell became an influential critic, scholar and arts activist. Even though Abell’s efforts to nationalize Maritime art institutions and initiatives can be seen to have contributed to central-Canadian domination of cultural institutions, it should be recognized that Abell understood his actions very differently and that he thought his Maritime-based experiments in what he called “cultural democracy” could be expanded across the country. Abell’s perception, however, that his goal of a participatory, cooperative, community-based culture was the common aim of Canada’s elites and institutions was perhaps his greatest misjudgment. Résumé Pendant son séjour en Nouvelle-Écosse, Walter Abell acquit une influence à titre de critique, d’universitaire et d’activiste artistique. Bien que les efforts d’Abell pour nationaliser les institutions et les initiatives artistiques des Maritimes puissent sembler avoir contribué à la domination du centre du Canada sur les institutions culturelles, il faut reconnaître qu’Abell voyaient ses actions d’une tout autre façon et qu’il croyait que ses expériences réalisées aux Maritimes concernant ce qu’il appelait la “ démocratie culturelle” pouvaient s’étendre à tout le pays. Toutefois, la plus grande erreur de jugement d’Abell fut peut-être d’avoir cru que son objectif d’une culture fondée sur la participation et la collaboration de la communauté était le but commun visé par les élites et les institutions canadiennes.